Aerogels as promising materials for antibacterial applications: a mini-review. (12th October 2021) - Guzel Kaya, Gulcihan; Aznar, Elena; Deveci, Huseyin; Martínez-Máñez, Ramón
Abstract : Aerogels with ultra-low density, high porosity, tunable sizes, and biocompatibility have been regarded as promising carriers for antibacterial applications. Different approaches can be followed to obtain such beneficial antibacterial activity. Abstract : The increasing cases of bacterial infections originating from resistant bacteria are a serious problem globally and many approaches have been developed for different purposes to treat bacterial infections. Aerogels are a novel class of smart porous materials composed of three-dimensional networks. Recently, aerogels with the advantages of ultra-low density, high porosity, tunable particle and pore sizes, and biocompatibility have been regarded as promising carriers for the design of delivery systems. Recently, aerogels have also been provided with antibacterial activity through loading of antibacterial agents, incorporation of metal/metal oxides and via surface functionalization and coating with various functional groups. In this mini-review, the synthesis of aerogels from both conventional and low-cost precursors is reported and examples of aerogels displaying antibacterial properties are summarized. As a result, it is clear that the encouraging antibacterial performance of aerogels promotes their use in many antibacterial applications, especially in the food industry, pharmaceutics and medicine.